- Assessment of Nature and Cultural Conservation and Achievement of The SDGS in The Hargotirto Tourism Village Area, Kulonprogo - Muhamad, Muhamad; Aznem, Ahmad (Jurnal Toursci, 2024)
The government continues to encourage the development and development of tourism in Indonesia, which is oriented towards regional development that relies on the community and is empowering the community, which includes various aspects, such as human resources, marketing, destinations, science and technology, cross-sector linkages, cooperation between countries, empowerment of small businesses, and responsibility in the utilization of natural and cultural resources. The main purpose of this study is to assess the preservation of nature and culture as an asset of a tourist village in Hargotirto, Kulonprogo. The study method is carried out using a qualitative descriptive data analysis technique, which is a research method that utilizes qualitative data and describes it descriptively. This type of qualitative descriptive data analysis is frequently used to analyze events, phenomena, or circumstances in a social way. The assessment results were carried out on Water Resources Management, Water Use Management System, Waste Management, Waste Management, and Waste Management, which have varying levels of importance.